Pengaruh Senam Berirama Terhadap Kemampuan Motorik Siswa Kelas IV SDN 025 Palembang - Muhammad Rizki Alfando; Ilham Arvan Junaidi; Rury Rizhardi (SENTRI: Jurnal Riset Ilmiah, 2026)
The problem in this study is the low motoric abilities of students of SDN 025 Palembang. This study aims to determine whether there is an Effect of Rhythmic Gymnastics on the Motoric Abilities of Fourth Grade Students of SDN 025 Palembang. This study uses quantitative Pre-Experimental research with a One Group Pretest-Posttest design. The population in this study were all fourth grade students of SDN 025 Palembang and the sample in the study was the fourth grade class. B. Data collection techniques in this study were tests used to measure students' motoric abilities. Hypothesis testing used a paired sample t-test. Based on the results of the hypothesis test calculation, a significance value (Sig. 2-tailed) of 0.000 <0.05 was obtained. This indicates that Ho is rejected and Ha is accepted. So it can be concluded that there is an effect of rhythmic gymnastics on the motoric abilities of fourth grade students of SDN 025 Palembang.